2017
DOI: 10.1002/jqs.2941
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Loch Lomond Stadial (Younger Dryas) glaciers on Ben More Coigach, north-west Scotland, and implications for reconstructing palaeoclimate using small ice masses

Abstract: A significant inventory of evidence exists for Loch Lomond Stadial (LLS; ≈Younger Dryas) glaciation in Scotland, with recent work focused on satellite icefields. However, studies of more marginal settings are important for assessing the influence of topoclimatic factors on glacier functioning and, crucially, the impact of these on glacier‐derived palaeoclimatic reconstructions. We present systematic assessments of snowblow and avalanching contributions, informed by modern analogues, and test these using the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 130 publications
0
25
1
Order By: Relevance
“…snowblow, avalanching, topographic shading) can play an important role in augmenting glacier mass balance and lowering ELAs (e.g. Sissons and Sutherland, 1976;Mitchell, 1996;Nesje and Dahl, 2000;Coleman et al, 2009;Mills et al, 2009Mills et al, , 2012Chandler and Lukas, 2017). Previous Scottish studies have shown that an eastward decline in ELAs is a characteristic feature of many Younger Dryas icefields, including the neighbouring Drumochter Icefield.…”
Section: Equilibrium Line Altitude Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…snowblow, avalanching, topographic shading) can play an important role in augmenting glacier mass balance and lowering ELAs (e.g. Sissons and Sutherland, 1976;Mitchell, 1996;Nesje and Dahl, 2000;Coleman et al, 2009;Mills et al, 2009Mills et al, , 2012Chandler and Lukas, 2017). Previous Scottish studies have shown that an eastward decline in ELAs is a characteristic feature of many Younger Dryas icefields, including the neighbouring Drumochter Icefield.…”
Section: Equilibrium Line Altitude Reconstructionmentioning
confidence: 99%
“…7 and 9), snow may have been transferred to the former glacier surface through snowblow from the plateau, thereby augmenting glacier mass balance and lowering the ELA (cf. Coleman et al, 2009;Mills et al, 2009Mills et al, , 2012Chandler and Lukas, 2017). In addition, the Glas Glacier catchment contains a substantial basin -one of the few well-developed cirques in the area -that could have allowed the preferential accumulation of snow from snow-bearing winds from the northwest to north.…”
Section: Equilibrium Line Altitude Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of the range of landform-sediment assemblages have been provided for a number of modern and palaeoglacial environments, including in low-latitude (e.g. Benn, 1989;Kirkbride, 2000;Glasser and Hambrey, 2002;Deline and Orombelli, 2005;Roberson, 2008;Burki et al, 2009;Lukas, 2012;Bendle and Glasser, 2012;Chandler and Lukas, 2017), and high-latitude (e.g. Benn, 1989;Kirkbride, 2000;Glasser and Hambrey, 2002;Deline and Orombelli, 2005;Roberson, 2008;Burki et al, 2009;Lukas, 2012;Bendle and Glasser, 2012;Chandler and Lukas, 2017), and high-latitude (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Benn and Owen, 2002;Owen et al, 2003), mid-latitude (e.g. Benn, 1989;Kirkbride, 2000;Glasser and Hambrey, 2002;Deline and Orombelli, 2005;Roberson, 2008;Burki et al, 2009;Lukas, 2012;Bendle and Glasser, 2012;Chandler and Lukas, 2017), and high-latitude (e.g. Fitzsimons, 2003;Glasser and Hambrey, 2003;Lukas et al, 2005;Evans et al, 2006aEvans et al, , 2016bEvans, 2010;Brynjólfsson et al, 2012) settings.…”
Section: Introductionmentioning
confidence: 99%